Polymorphisms in intron 1 of HLA-DRA differentially associate with type 1 diabetes and celiac disease and implicate involvement of complement system genes C4A and C4B - Aydemir, Ozkan; Bailey, Jeffrey A.; Agardh, Daniel; Lernmark, Ake; Noble, Janelle A.; Andersson Svard, Agnes; Blankenhorn, Elizabeth P.; Parikh, Hemang M.; Ziegler, Anette-G; Toppari, Jorma; Akolkar, Beena; Hagopian, William A.; et al. (eLife Sciences Publications, 2026)
Polymorphisms in genes in the human leukocyte antigen (HLA) class II region comprise the most important inherited risk factors for many autoimmune diseases, including type 1 diabetes (T1D) and celiac disease (CD): both diseases are positively associated with the HLA-DR3 haplotype (DRB1*03:01-DQA1*05:01-DQB1*02:01). Studies of two different populations have recently documented that T1D susceptibility in HLA-DR3 homozygous individuals is stratified by a haplotype consisting of three single nucleotide polymorphisms (‘tri-SNP’) in intron 1 of the HLA-DRA gene. In this study, we use a large cohort from the longitudinal ‘The Environmental Determinants of Diabetes in the Young’ (TEDDY) study to further refine the tri-SNP association with T1D and with autoantibody-defined T1D endotypes. We found that the tri-SNP association is primarily in subjects whose first-appearing T1D autoantibody is to insulin. In addition, we discovered that the tri-SNP is also associated with CD, and that the particular tri-SNP haplotype (‘101’) that is negatively associated with T1D risk is positively associated with risk for CD. The opposite effect of the tri-SNP haplotype on two DR3-associated diseases can enhance and refine current models of disease prediction based on genetic risk. Finally, we investigated possible functional differences between the individuals carrying high and low-risk tri-SNP haplotypes and found that differences in complement system genes C4A and C4B may underlie the observed divergence in disease risk.